(untitled) (Hematology Meeting Reports, 2009)
The introduction of monoclonal antibodies into the therapeutic arena in chronic lymphocytic leukemia (CLL) has revolutionize the possibility of effective treatment of this indolent condition. The impressive activity of rituximab in the management of lymphoma was obvious early. The usefulness of this antibody in CLL was not as apparent, as in the pivotal clinical trial, small lymphocytic lymphoma (SLL) patients in relapse had a response rate of only 12%. Alemtuzumab when used initially had impressive antitumor activity but very significant toxicity. These two agents are however been built into effective treatment strategies at all ends of the therapeutic spectrum in CLL.